An investigation of how code switching between English and Oshiwambo enables or constrains teaching and learning of 'force' in Grade 7 Natural Science and Health Education in a rural Namibian school - Nambahu, Paulus Tulimekondjo (Rhodes University, Faculty of Education, Department of Education, 2017)
Anecdotal evidence over the years of my teaching reveals the use of code switching to be a regular practice in rural schools in the northern part of Namibia. Some recent studies focused on how Namibian teachers mediate specific science topics through code switching. However, although the 2013 Grade 10 examiners' report and the latest (2014) Grade 7 National Standardized Achievement Test (NSAT) indicate that learners performed poorly in the important science topic Force, no literature could be found which explored this problem in Namibian science education. This triggered my interest to investigate how the use of code switching between English and Oshiwambo enables or constrains teaching and learning of the topic Force in Natural Science and Health Education (NSHE) lessons at a rural Namibian school. I accomplished this by implementing strategic code switching as an intervention in my own teaching with a class of Grade 7 NSHE learners and with the participation of a critical friend. An initial action research cycle of teaching was done in the medium of instruction (English) without any code switching and a Pre-test was then administered to assess learners understanding prior to the intervention. After this first cycle, code switching was integrated into the teaching as an intervention in the second cycle of teaching in the action research and a Post test was then administered. This research study is informed by social constructivism theory of Vygotsky (1978) with a focus on the concept of Zone of Proximal Development (ZPD) using language as a tool for mediating learning through strategic code switching as an aspect of Pedagogical Content Knowledge (PCK). The two action research cycles included me undertaking regular and in-depth reflections after my teaching of each lesson. Data were also collected through document analysis, learners' responses to tests, lesson observation with video recording and stimulated recall interviews. The analysis of the data involved qualitative coding of data. Informed consent of all participants was sought by obtaining signed written informed consent letters from parents of learners taking part in the study, as well as from the teacher participating as a critical friend, the school governing body and the regional director of education, arts and culture. Findings from this study revealed that code switching between English and Oshiwambo as a teaching intervention influenced learners performance positively. The results reveal that when code switching, linguistic, dispositional, hands-on experience and relating abstract concepts to everyday life experience were either enabling or constraining factors for learning the concept Force. Furthermore, the study reveals reinforcement and relating abstract concepts to everyday life world as an enabling factor for teaching the concept Force, when code switching. Linguistic and time have been identified as constrain factors when teaching Force through code switching. Finally, it was evident that when teaching and learning is mediated through code switching some factors are enabling when/if present but constraining when/if they are absent. The results from this study have the potential to enhance my own teaching practice as well the practice of other science teachers in similar education contexts.
Keywords: Uncatalogued